2022
DOI: 10.1155/2022/8916076
|View full text |Cite|
|
Sign up to set email alerts
|

Effect Evaluation of Platelet-Rich Plasma Combined with Vacuum Sealing Drainage on Serum Inflammatory Factors in Patients with Pressure Ulcer by Intelligent Algorithm-Based CT Image

Abstract: This work was to explore the efficacy of intelligent algorithm-based computed tomography (CT) to evaluate platelet-rich plasma (PRP) combined with vacuum sealing drainage (VSD) in the treatment of patients with pressure ulcers. Based on the u-net network structure, an image denoising algorithm based on double residual convolution neural network (Dr-CNN) was proposed to denoise the CT images. A total of 84 patients who were hospitalized in hospital were randomly divided into group A (without any intervention), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Conventional treatment has been unable to achieve good clinical effects, and may lead to the exacerbation of the disease and the prolongation of the course of the disease [ 18 ]. Patients need long-term dressing changes, which brings adverse effects on their physical and mental health and quality of life [ 19 , 20 ]. In this study, 110 PU patients admitted to our hospital from January 2021 to January 2023 were included as research objects, and were randomly divided into the Exp group and the Ctrl group by blind selection, with 55 cases in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatment has been unable to achieve good clinical effects, and may lead to the exacerbation of the disease and the prolongation of the course of the disease [ 18 ]. Patients need long-term dressing changes, which brings adverse effects on their physical and mental health and quality of life [ 19 , 20 ]. In this study, 110 PU patients admitted to our hospital from January 2021 to January 2023 were included as research objects, and were randomly divided into the Exp group and the Ctrl group by blind selection, with 55 cases in each group.…”
Section: Discussionmentioning
confidence: 99%
“…Pressure ulcers are one of the most common ailments in patients with chronic diseases or other factors that cause them to be bedridden for long periods of time, and the incidence is higher in older patients 1 . The main reason for the occurrence of pressure ulcers is that the patient's local tissues are in a state of pressure for a long period of time, and the blood circulation is affected, so that the local tissues are in a state of long‐term hypoxia and ischaemia, resulting in ulceration and local necrosis 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcers are one of the most common ailments in patients with chronic diseases or other factors that cause them to be bedridden for long periods of time, and the incidence is higher in older patients. 1 The main reason for the occurrence of pressure ulcers is that the patient's local tissues are in a state of pressure for a long period of time, and the blood circulation is affected, so that the local tissues are in a state of long‐term hypoxia and ischaemia, resulting in ulceration and local necrosis. 2 , 3 Moreover, due to the continuous compression of local tissues, such ulceration is not easy to heal and readily becomes infected, and in serious cases, it may also lead to sepsis, which affects the patient's quality of life and may be life‐threatening.…”
Section: Introductionmentioning
confidence: 99%
“… 7–9 L-PRP also exhibited positive effect on few PU trails. 10 , 11 Nevertheless, some studies indicated that leukocytes may impose detrimental effects on tissue healing instead due to their role in the release of inflammatory cytokines and increased matrix metalloproteinases (MMP) levels. 12–14 As there was no head-to-head study between L-PRP and P-PRP, no evidence is currently available to compare the effectiveness of both on PU.…”
mentioning
confidence: 99%